2014
DOI: 10.1002/anie.201402868
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine‐Directed CH Borylation Reactions: Facile and Selective Access to Ambiphilic Phosphine Boronate Esters

Abstract: Ambiphilic ligands have received considerable attention over the last two decades due to their unique reactivity as organocatalysts and ligands. The iridium-catalyzed C-H borylation of phosphines is described in which the phosphine is used as a directing group to provide selective formation of arylboronate esters with unique scaffolds of ambiphilic compounds. A variety of aryl and benzylic phosphines were subjected to the reaction conditions, selectively providing stable, isolable boronate esters upon protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
70
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(72 citation statements)
references
References 50 publications
1
70
0
1
Order By: Relevance
“…In 2014, Clark et al demonstrated that P III could act as ad irecting group in Ir I -catalyzed CÀHb ond borylation of JohnPhos derivatives. [11] In 2019, Takayasa nd Shisg roups independently reported the ortho-borylation of triarylphosphines using Ru II or Rh I catalysis. [12] In 2017, Shisg roup reported the Rh I -catalyzed CÀHb ond arylation of biarylphosphines at the ortho' position, thus offering efficient access to triarylphosphines.…”
mentioning
confidence: 99%
“…In 2014, Clark et al demonstrated that P III could act as ad irecting group in Ir I -catalyzed CÀHb ond borylation of JohnPhos derivatives. [11] In 2019, Takayasa nd Shisg roups independently reported the ortho-borylation of triarylphosphines using Ru II or Rh I catalysis. [12] In 2017, Shisg roup reported the Rh I -catalyzed CÀHb ond arylation of biarylphosphines at the ortho' position, thus offering efficient access to triarylphosphines.…”
mentioning
confidence: 99%
“…[9] However,i nm ost of the cases,t he phosphorus atom has to be oxidized to act as aP V directing group. [11] In 2019, Takayasa nd Shisg roups independently reported the ortho-borylation of triarylphosphines using Ru II or Rh I catalysis. In 2014, Clark et al demonstrated that P III could act as ad irecting group in Ir I -catalyzed CÀHb ond borylation of JohnPhos derivatives.…”
mentioning
confidence: 99%
“…[2e, 4] However, most directing groups are difficult to remove after the introduction of the boryl group. To address this issue, our group developed silyl-directed borylations of C-H bonds (Scheme 1c).…”
mentioning
confidence: 99%
“…Because rhodium complexes containing phosphines also catalyze the borylation of aromatic C-H bonds, [3c, 4d] we tested various combinations of rhodium precursors and chiral phosphines as catalyst for the enantioselective borylation (for details, see Supporting Information). However, no conversion was observed for reactions conducted with any of the rhodium catalysts generated from [Rh(cod)Cl] 2 and chiral bisphosphine ligands.…”
mentioning
confidence: 99%